2021
DOI: 10.1021/acsomega.1c01978
|View full text |Cite
|
Sign up to set email alerts
|

Xylan Structure and Dynamics in Native Brachypodium Grass Cell Walls Investigated by Solid-State NMR Spectroscopy

Abstract: The polysaccharide composition and dynamics of the intact stem and leaf cell walls of the model grass Brachypodium distachyon are investigated to understand how developmental stage affects the polysaccharide structure of grass cell walls. 13 C enrichment of the entire plant allowed detailed analysis of the xylan structure, side-chain functionalization, dynamics, and interaction with cellulose using magic-angle-spinning solid-state NMR spectroscopy. Quantitative one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…A clear difference in grass compared to dicot SCW is that the FA on GAX covalently bonds lignin via oxidative coupling, although the extent of this is difficult to determine (Ralph, 2010). GAX-FA is abundant on both Xn 2f and Xn 3f conformations in Brachypodium stems, and the authors proposed a model of grass SCW where FA on Xn 2f bound to cellulose crosslinks with other xylan FAs, and FA on Xn 3f covalently links to lignin (Duan et al, 2021). This model fits with several lines of evidence that show the abundance of GAX-FA and linkage of FA to lignin are correlated with recalcitrance to digestion of grass biomass (reviewed in (Buanafina, 2009;de Oliveira et al, 2015;Terrett and Dupree, 2019)).…”
Section: Hydroxycinnamate Modification Of Xylanmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear difference in grass compared to dicot SCW is that the FA on GAX covalently bonds lignin via oxidative coupling, although the extent of this is difficult to determine (Ralph, 2010). GAX-FA is abundant on both Xn 2f and Xn 3f conformations in Brachypodium stems, and the authors proposed a model of grass SCW where FA on Xn 2f bound to cellulose crosslinks with other xylan FAs, and FA on Xn 3f covalently links to lignin (Duan et al, 2021). This model fits with several lines of evidence that show the abundance of GAX-FA and linkage of FA to lignin are correlated with recalcitrance to digestion of grass biomass (reviewed in (Buanafina, 2009;de Oliveira et al, 2015;Terrett and Dupree, 2019)).…”
Section: Hydroxycinnamate Modification Of Xylanmentioning
confidence: 99%
“…In lignified secondary cell walls (SCW) of both grasses and dicots, solid-state NMR suggests xylan in a twofold screw conformation (Xn 2f ) binds to cellulose microfibrils ( Simmons et al., 2016 ); whereas, distorted twofold or threefold screw xylan (Xn 3f ) interacts closely with lignin ( Kang et al., 2019 ; Duan et al., 2021 ). Thus, xylan bridges the two main components of SCW, although a study on sorghum SCW suggested Xn 2f was much less prevalent there ( Gao et al., 2020 ).…”
Section: Background - Importance Of Cell Wall Hydroxycinnamatesmentioning
confidence: 99%
“…A higher proportion of xylan functional groups (ferulic acid, FA, and acetyl, Ac) promotes its 2-fold conformation and contacts with cellulose fibrils. Panel E is adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Solid-state Nmr Studies Of Plant Materialsmentioning
confidence: 99%
“…260 The conformational dependence of xylan's function was also confirmed in a recent study on 7-week-old Brachypodium (a model grass). 306 The structure and interactions of xylans were compared between the leaves and the stems, with the latter containing more secondary cell walls. Xylan chains were found to have twice as much acetylation and 60% more ferulation in the stems than in the leaves.…”
Section: Polymer Contacts In Secondary Cell Wallsmentioning
confidence: 99%
“…Cellular samples can be assessed using in situ solid-state nuclear magnetic resonance (ssNMR), an emerging nondestructive method with atomic to nanoscale resolution complementing X-ray diffraction and electron microscopy techniques . SsNMR has enabled high-resolution characterization of bacterial cells, plant tissues, , fungal mycelia and cells, mammalian cells, viral particles, , and recently algal cultures under MAS conditions.…”
Section: Introductionmentioning
confidence: 99%